The statesman's science : history, nature, and law in the political thought of Samuel Taylor Coleridge - Edwards, Pamela, 1956- (Columbia University Press, 2004)
Author of "Kubla Khan" and the epic "The Rime of the Ancient Mariner," Samuel Taylor Coleridge is remembered principally for his contributions as a romantic poet. This innovative reconsideration of Coleridge's thought and career not only demonstrates his importance as a philosopher but also recovers romanticism as both an aesthetic and a political movement. Pamela Edwards radically departs from classic theories of Coleridge's development and reads his writing within the framework of a constantly shifting political and social landscape.